Giant anisotropic piezoresponse of layered ZrSe3 - Radatović, Borna; Li, Hao; D'Agosta, Roberto; Castellanos-Gomez, Andres (Nanoscale horizons, 2025)
We investigated the effect of uniaxial strain on the electrical properties of few-layer ZrSe3 devices under compressive and tensile strains applied up to ±0.62% along different crystal directions. We observed that the piezoresponse, the change in resistance upon application of strain, of ZrSe3 strongly depends on both the direction in which electrical transport occurs and the direction in which uniaxial strain is applied. Notably, a remarkably high anisotropy in the gauge factor for a device with the transport occurring along the b-axis of ZrSe3 with GF = 68 when the strain is applied along the b-axis was obtained, and GF = 4 was achieved when strain is applied along the a-axis. This leads to an anisotropy ratio of almost 90%. Devices whose transport occurs along the a-axis, however, show much lower anisotropy in gauge factors when strain is applied along different directions, leading to an anisotropy ratio of 50%. Furthermore, ab initio calculations of strain dependent change in resistance showed the same trends of the anisotropy ratio as obtained from experimental results for both electrical transport and strain application directions, which were correlated with bandgap changes and different orbital contributions.